Pelatihan Mental Health dalam Menjalankan Bisnis bagi UMKM - Appin purisky redaputri; Niki Agus Santoso; Aprinisa Aprinisa; Shanaz Rizkyna (LP4MK STKIP PGRI Lubuklinggau, 2024)
The purpose of this study was to explore the importance of mental health among entrepreneurs and employees in Micro, Small and Medium Enterprises (MSMEs) in the context of post-COVID-19 pandemic recovery. The methods used included the development of a training program designed to improve mental health literacy. The results showed that many workers in MSMEs experienced increased stress and anxiety due to the impact of the pandemic, with many workers losing their jobs. Effective mental health training can increase knowledge and reduce stigma related to mental health issues, as well as build support networks among entrepreneurs. In conclusion, comprehensive mental health interventions are essential to improve psychological well-being and productivity in MSMEs, as well as support business resilience in the face of existing challenges.